Rủi ro hệ thống của các ngân hàng thương mại Việt Nam - Phương pháp CCA - Hạ Thị Thiều , Dao; Châu Hồ Quốc , Bảo; Lê Nguyễn Minh , Phương; Lê Thị Hồng , Gấm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This study measures the systemic risk of commercial banks in Vietnam and analyses its factors. The contingent claim approach (CCA) is employed to measure the systemic risk of Vietnam banking system over the period 2007–2018. Moreover, by employing a Panel Vector Autoregressive model (Panel VAR) with generalized method of moments (GMM) estimate method, combined with Granger causality test, impulse response function, and variance decomposition, the research shows that an increase in mobilization capital, an increase in non-performing loans and ineffective systemic risk management may cause an increase in systemic risk. In addition, some suggestions about important policy implications for authorities are discussed with the findings in order to control the factors of systemic risk as well as avoid the adverse consequences for the economy.